Lectotypification of some names in the Jovibarba heuffelii group (Crassulaceae) - Nikolić, Danijela; Kuzmanović, Nevena; Walter, Johannes; Lakušić, Dmitar; Randelović, Vladimir; Letz, Dominik Roman (Phytotaxa, 2014)
A taxonomic revision of the highly variable Jovibarba heuffelii group needs a proper typification of the names of the taxa described. The following names are lectotypified and shortly discussed: Diopogon stramineus, Sempervivum ciliatum, S. heuffelii, S. heuffelii var. glabrum, S. kopaonikense, S. patens and S. velenovskyi. Pictures of the type specimens are also provided. Other names recorded in the synonymy of J. heuffelii [Sempervivum brassaii Schur (1866: 229), S. heuffelii var. albanicum Kitanov (1948: 200), S. heuffelii var. bulgaricum Cheshmedjiev (1969: 474), S. heuffelii var. vestitum Domin (1933: 17), S. reginae-amaliae Heldreich & Sarnthein ex Baker (1877: 230), S. transylvanicum Baker (1874: 104)] are also commented.